49.5k views
2 votes
The explicit rule for a sequence is given

an=1/2 (4/3) n-1

Enter the recursive rule for the geometric sequence

A1=???

An=???

2 Answers

4 votes

Answer:

4/3an−1

Explanation:

I followed someone elses answer and it was wrong so this one is right :)

The explicit rule for a sequence is given an=1/2 (4/3) n-1 Enter the recursive rule-example-1
User JoeFox
by
4.8k points
4 votes
ANSWER


image

EXPLANATION

The explicit rule for the given geometric sequence is


a_n = (1)/(2) ( (4)/(3) ) ^(n - 1)

The first term of the geometric sequence can be obtained by substituting n=1.


a_1= (1)/(2)((4)/(3) )^(1 - 1)


a_1= (1)/(2) ( (4)/(3) )^(0)


a_1= (1)/(2)

The common ratio is


(4)/(3)

To get the subsequent terms we multiply the previous terms by


(4)/(3)

The recursive rule is therefore,


image
User TobyG
by
5.0k points